Azo dye adsorption on ZrO2 and natural organic material doped ZrO2 - Sedef Sismanoglu; Erdem Buran (Scientific Reports)
Abstract Natural wastes and inorganic adsorbents are used for the removal of diazo dye Congo red (CR), which causes water pollution and is a carcinogen, from wastewater. Organic waste olive pulp (ZK), inorganic ZrO2 (Zr) and three different weight percent ZK/Zr (organic/inorganic) binary adsorbent systems prepared by ball-milling method were investigated for the effective removal of CR from wastewater. Characterization of both single and binary adsorbent systems were carried out by ATR/FTIR and SEM. According to the Langmuir isotherm, qmax values for ZK, Zr, 25ZK-75Zr, 50ZK-50Zr and 75ZK-25Zr at 45 °C were 588 mgg-1, 13 mgg-1, 46 mgg-1, 65 mgg-1 and 84 mgg-1, respectively. According to Frumkin-Fowler–Guggenheim and Temkin isotherms, the adsorption heat was found to be exothermic for ZK and 75ZK-25Zr at all three temperatures, while it was found to be endothermic for Zr, 25ZK-75Zr and 50ZK-50Zr. It was observed that the ΔG° values calculated from the thermodynamic data were consistent with the values in the Flory-Huggings isotherm. According to the kinetic data, it was observed that all adsorbents except ZK obeyed the pseudo-first-order rate equation. It was shown by error calculations that the experimental data obeyed the Langmuir or Freundlich isotherms better. It was observed that a new and effective organic/inorganic adsorbent system could be obtained by adding ZK to ZrO2 for the removal of Congo red (CR) from water.